Morphometric delimitation of Pterinopelma longisternale (Bertani, 2001) and Pterinopelma roseum (Mello-Leitão, 1923) (Mygalomorphae, Theraphosidae) - Moeller, Wolf [UNESP]; Galleti-Lima, Arthur [UNESP]; Guadanucci, José Paulo Leite [UNESP] (Taylor & Francis, 2024)
Delimiting morphological characters for phylogenetic studies in Mygalomorphae taxa can be challenging due to their conservative morphology, oftenresulting in the establishment of diagnoses with overlapping characters of continuous variation. The Theraphosidae species P. longisternale and P. roseum are considered sister species and the main diagnostic character to distinguish them is the sternum length. We tested the significance of this character in distinguishing these two species using the landmark-based analysis to explore the sternum morphometric variations. Our results showed that sternum shape variations between P. longisternale and P. roseum are continuous and can be differentiated by the width x length ratio, although they are associated with other diagnostical characters, as the size of the branches of the tibial apophysis and the palpal bulb subapical keel.
Keywords: continuous characters; landmarks; Morphometry; Mygalomorphae; species delimitation